Potential for application of hydroxyapatite-based bone grafting materials in spine surgery - U. F. Mukhametov; S. V. Lyulin; D. Yu. Borzunov (Креативная хирургия и онкология)
The expansion in the number of primary joint replacements worldwide is causing a rise in revision joint replacements due to bacterial infection. Revision surgery with cementless implants appears to be beneficial for long-term outcome, and using antibiotic-impregnated bone grafts can control infection and provide good implant support. Autologous bone graft s (autografts) areused in surgery to fill defects and impaction bone grafting in spinal reconstruction. Because of their superior osteoinductive ability, autograft sare considered the “gold standard” for these treatments. However, due to a better cost-benefit ratio, allografts are also often used. In case of limited donor availability for autologous or allogeneic bone graft s, bone grafting materials are a reasonable alternative or adjunct. Bone grafting materials combine or are based on different substances. Growth factors of the bone morphogenetic protein family are recombinant proteins that specifically induce bone and cartilage growth. One advantage of bone grafting materials is that they can be combined with several antibiotics. Th e choice of antibiotics should consider possible dose-dependent cellular and pharmacological side effects at the implantation site, as well as be based on antimicrobial efficacy. Thus, microbiologists, pharmacologists and surgeons must decide together which combination is more appropriate. Bone grafting materials with active ingredient supplements are considered to be combination drugs, characterised by a primary effect (bone replacement function) and a secondary effect (prevention of bacterial recolonization of the bone grafting materials). Both functions must be clinically validated during the registration process as a Class III medical device. Currently, only a few combination products are available on the market. In this review, we considered the existing hydroxyapatite-based bone grafting materials and the potential for their use in spine surgery.